Monoclonal antibody against Nile tilapia (Oreochromis niloticus) IgM heavy chain: A valuable tool for detection and quantification of IgM and IgM+ cells. Issue 110 (March 2021) - Velázquez, Janet; Rodríguez, Alianet; Aragón, Hasel; Haidar, Arlette; González, Marcos; Valdés, Rodolfo; Garay, Hilda Elsa; Abreu, David Diago; Ramos, Yassel; Cabrales, Ania; Morales, Antonio; González, Osmany; et al.
Abstract: Nile tilapia ( Oreochromis niloticus ) is a freshwater fish, which is extensively cultivated worldwide and constitutes one of the model species for the study of fish immunology. Monoclonal antibodies are very advantageous molecular tools for studying teleost immune system. Specifically, monoclonal antibodies that react with immunoglobulins are used successfully in the study of the humoral immune response of several fish species. In the present study, we produced and characterized a monoclonal antibody against tilapia IgM heavy chain using a peptide-based strategy. The peptide sequence was selected from the surface-exposed region between CH3–CH4 domains. The specificity of the polyclonal serum and the hybridoma culture supernatant obtained by immunization with the peptide conjugated to keyhole limpet hemocyanin were evaluated by western blotting, both showing reactivity against tilapia serum IgM. The purified mAb was able to recognize secreted IgM by western blotting and ELISA and membrane IgM by flow cytometry. We also demonstrated that the antibody doesn't cross-react with a recombinant IgT fragment. This tool allowed us to study for the first time the stimulation of mucosal immunity after Pituitary Adenylate Cyclase Activating Polypeptide administration. Overall, the results demonstrated the utility of this mAb to characterize humoral immune response in O. niloticus . Highlights: MAb against Nile tilapia IgM using a peptide-based strategy was produced and characterized. Nile tilapia IgM purified from serum was successfully identified by mass spectrometry analysis. The produced mAb was specific for IgM and doesn't cross-react with a recombinant IgT fragment. The prepared mAb is applicable for IgM detection and quantification by western blotting, ELISA and flow cytometry. IgM and IgT concentrations increased in tilapia skin mucus after injection of synthetic C. gariepinus PACAP-38.